CBCT‐based assessment of the anatomic relationship between maxillary sinus and upper teeth. Issue 6 (22nd May 2021) - Regnstrand, Tobias; Torres, Andres; Petitjean, Eline; Lambrechts, Paul; Benchimol, Daniel; Jacobs, Reinhilde
Abstract: Objectives: To describe the relationship between maxillary sinus (MS) and upper teeth based on cone beam computed tomographic scans (CBCT). Materials and methods: Based on CBCT maxillary imaging data of 147 patients, distance between MS and apices of canines and posterior maxillary teeth were assessed. Distances between tooth roots and sinus were classified into three groups: distant (>2 mm), close (<2 mm) or in contact with MS. Teeth with apical lesions and uncommon root configurations were excluded. Results: In total, 1075 teeth of maxillary canines, upper premolars and upper molars were included in this study. Teeth most often in contact with MS were the second (89%) and first (81%) maxillary molar without any significant difference ( p = 0.19). Roots most often in contact with MS were the mesiobuccal and distobuccal root of the second molar (85% and 76%; p = <0.01) followed by the palatal root of the first molar (73%). A fifth of the upper canines are situated less than 2 mm from MS. Conclusions: More than four out of five upper molars (first and second) are in a close relationship to the MS. Knowledge of the anatomical relationship between posterior maxillary teeth and the MS is important for diagnosis and treatment in this area.